E2F1 promotes hepatic gluconeogenesis and contributes to hyperglycemia during diabetes - Albert Giralt; Pierre-Damien Denechaud; Isabel C. Lopez-Mejia; Brigitte Delacuisine; Emilie Blanchet; Caroline Bonner; Francois Pattou; Jean-Sébastien Annicotte; Lluis Fajas (Elsevier, 2018)
Objective: Aberrant hepatic glucose production contributes to the development of hyperglycemia and is a hallmark of type 2 diabetes. In a recent study, we showed that the transcription factor E2F1, a component of the cell cycle machinery, contributes to hepatic steatosis through the transcriptional regulation of key lipogenic enzymes. Here, we investigate if E2F1 contributes to hyperglycemia by regulating hepatic gluconeogenesis. Methods: We use different genetic models to investigate if E2F1 regulates gluconeogenesis in primary hepatocytes and in vivo. We study the impact of depleting E2F1 or inhibiting E2F1 activity in diabetic mouse models to evaluate if this transcription factor contributes to hyperglycemia during insulin resistance. We analyze E2F1 mRNA levels in the livers of human diabetic patients to assess the relevance of E2F1 in human pathophysiology. Results: Lack of E2F1 impaired gluconeogenesis in primary hepatocytes. Conversely, E2F1 overexpression increased glucose production in hepatocytes and in mice. Several genetic models showed that the canonical CDK4-RB1-E2F1 pathway is directly involved in this regulation. E2F1 mRNA levels were increased in the livers from human diabetic patients and correlated with the expression of the gluconeogenic enzyme Pck1. Genetic invalidation or pharmacological inhibition of E2F1 improved glucose homeostasis in diabetic mouse models. Conclusions: Our study unveils that the transcription factor E2F1 contributes to mammalian glucose homeostasis by directly controlling hepatic gluconeogenesis. Together with our previous finding that E2F1 promotes hepatic steatosis, the data presented here show that E2F1 contributes to both hyperlipidemia and hyperglycemia in diabetes, suggesting that specifically targeting E2F1 in the liver could be an interesting strategy for therapies against type 2 diabetes. Keywords: Gluconeogenesis, E2F1, Liver metabolism, Hyperglycemia, Diabetes, Cell cycle regulators